Effect of nitric oxide inhibitor and donor substances on the infammatory process caused by endodontic irrigants - Luciana Malheiro de Brito; Cláudia de Moura Carreira; Denise Pontes Raldi; José Luiz Lage-Marques; Sandra Márcia Habitante; Wilson Abraão Saad (University of São Paulo, 2011)
Nitric oxide (NO) has been considered a key molecule in infammation. OBJECTIVE: The aim of this study was to evaluate the effect of treatment with L-NAME and sodium nitroprussiate, substances that inhibit and release NO, respectively, on tissue tolerance to endodontic irrigants. MATERIAL AND METHODS: The vital dye exudation method was used in a rat subcutaneous tissue model. Injections of 2% Evans blue were administered intravenously into the dorsal penial vein of 14 male rats (200-300 g). The NO inhibitor and donor substances were injected into the subcutaneous tissue in the dorsal region, forming two groups of animals: G1 was inoculated with L-NAME and G2 with sodium nitroprussiate. Both groups received injections of the test endodontic irrigants: acetic acid, 15% citric acid, 17% EDTA-T and saline (control). After 30 min, analysis of the extravasated dye was performed by light absorption spectrophotometry (620 nm). RESULTS: There was statistically signifcant difference (p<0.05) between groups 1 and 2 for all irrigants. L-NAME produced a less intense infammatory reaction and nitroprussiate intensifed this process. CONCLUSIONS: Independently of the administration of NO inhibitors and donors, EDTA-T produced the highest irritating potential in vital tissue among the tested irrigating solutions.